Differentials in variables associated with past history of artificial abortion and current contraception by age: Results of a randomized national survey in Japan. Issue 3 (17th December 2016) - Kojo, Takao; Ae, Ryusuke; Tsuboi, Satoshi; Nakamura, Yosikazu; Kitamura, Kunio
Abstract: Aim: This study analyzes differentials in the variables associated with the experience of artificial abortion (abortion) and use of contraception by age among women in Japan. Methods: The 2010 National Lifestyle and Attitudes Towards Sexual Behavior Survey was distributed to 2693 men and women aged 16–49 selected from the Japanese population using a two‐stage random sampling procedure. From the 1540 respondents, we selected 700 women who reported having had sexual intercourse at least once. We used logistic regression to analyze how social and demographic factors were associated with the experience of abortion and contraceptive use. Results: The abortion rate according to the survey was 19.3%. Of the 700 women in the sample, 6.9% had experienced two or more abortions. Logistic regression revealed that, although significant variables depended on age, a high level of education and discussions about contraceptive use with partners were negatively associated with the experience of abortion. Self‐injury, approval of abortion and first sexual intercourse between the age of 10 and 19 were positively associated with the experience of abortion. Marriage, smoking and first sexual intercourse between the age of 10 and 19 were negatively associated with contraceptive use. Higher education and discussion of contraception with partners were positively associated with contraceptive use. Conclusions: To prevent unwanted pregnancy and abortion, social support and sexual education should be age‐appropriate. It is vital to educate young people of the importance of discussing contraceptive use with their partners.